Cardiohelp System use in school age children and adolescents at a center with interfacility mobile extracorporeal membrane oxygenation capability. Issue 2 (February 2022) - Ignat, Teodora; Desai, Ajay; Hoschtitzky, Andreas; Smith, Rosie; Jackson, Tim; Frall, Diane; Evans, Eleri; Trimlett, Richard; Ledot, Stephane; Chan-Dominy, Amy
Cardiohelp System use for pediatric extracorporeal membrane oxygenation (ECMO) beyond the transport setting is sparsely described in literature. We report the use of Getinge's Cardiohelp System in children and integrated utilization of Mobile ECMO Retrieval Team (MERT) at an all-age specialized cardiorespiratory center. Electronic database of all patients under 16 years of age who received ECMO with use of the Cardiohelp System between January 2018 and March 2020 was retrospectively reviewed and analyzed for demographics, set-up, complications, and outcomes. Out of 41 patients, seven patients (four in middle childhood, three in early teenage) with median age of 10 years (range 8.8–15.6) were supported with use of Cardiohelp System. Median weight and height were 34 kg (range 28–53) and 145 cm (range 134–166) respectively. Initial ECMO deployment was veno-arterial (V-A) in five patients and veno-venous (V-V) in two. There were three interhospital transfers by our MERT, and 12 intrahospital transfers for interventions or imaging. The median ECMO therapy was 7 days (range 4–25), with standard 3/8-inch tubing and ECMO flow rate range at 56–100 mL/kg/min (1.89–5.0 LPM). There were two circuit changes and three reconfigurations of support. Two patients received continuous veno-venous hemofiltration via ECMO circuit. The 90-day and 180-day survival rates were 100% (including two heart transplants at day 7 and day 8). There were no transport-related or circuit-related complications during the 1750 h of Cardiohelp use. Cardiohelp System use is safe in pediatric patients for diverse application of ECMO support including inter- and intrahospital transfers.